The applicability of 10 ml cryotubes for sperm cryopreservation in a Hungarian carp landrace (Cyprinus carpio carpio morpha accuminatus) - Várkonyi, Levente; Bokor, Zoltán; Ferincz, Árpád; Staszny, Ádám; Fodor, Ferenc; Szári, Zsolt; Urbányi, Béla; Molnár, József; Bernáth, Gergely (Acta Agraria Debreceniensis, 2018)
In our study, the comparison of 5 ml straw and 10 ml cryotube during sperm cryopreservation in a Hungarian carp landrace (Cyprinus carpio carpio morpha accuminatus) was carried out. Three different dilution ratios (1:1, 1:4 and 1:9) were also tested using the cryotube. A significantly higher pMOT was recorded using the cryotube in comparison with the straw. VCL and STR were similar in both groups. Cryopreservation had a negative effect on pMOT and VCl using the cryotube and also the straw where, STR was not reduced significantly. An increasing tendency was observed using higher dilution of sperm during cryopreservation; however, significant difference was not recorded between the three groups. VCL and STR were similar in all groups. Cryotube was applicable for the sperm cryopreservation of the Hungarian carp landrace. However, the standardization for the freezing method specified for this volume is recommended. The different dilution ratios needed be tested also during fertilization.